House prices and spatial mobility: Lock-in effects on the German rental market - Niklas Gohl (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
Since 2010, particularly in urban agglomerations, the German housing market has experienced stark house price and rent increases. Immigration from rural and smaller settlements as well as international migration into German urban areas, has fuelled an increase in housing demand and led to severe housing shortages in some parts of Germany. Incumbent tenants in these areas are often deemed lucky in the general public's discourse. Due to restrictions on rent increases within existing contracts, these sitting tenants pay rents significantly below the market level of new rental contracts whilst living in relatively popular areas. In the context of rising rents and house prices, this implies a growing residency discount, i.e. an increase in the gap of incumbent rents to new contract, market-level rents. However, long-term renting, in the context of changed circumstances from 2010 onwards, might also come at significant costs. Tenants who are dissatisfied with their home might not be capable of moving house or apartment as they may find themselves "locked-in". Using hedonic house price regressions and representative survey panel data, this paper will analyse whether residential mobility of sitting tenants in high rental and housing price areas is indeed restricted due to the aforementioned "lock-in effect".
Keywords: R00; R21; R30; R31; 330; spatial mobility; housing market; lock-in effects